Electrodeposition as a Versatile Preparative Tool for Perovskite Photovoltaics: Aspects of Metallization and Selective Contacts/Active Layer Formation. Issue 6 (3rd March 2022) - Di Girolamo, Diego; Dini, Danilo
Abstract : Perovskite‐based photovoltaics (PV) is expected to play a central role in sustainable energy production during the next decades. Several companies are investing intensively to develop a market‐ready product with efficiency and stability rapidly improving. The craft of making perovskite solar cells (PSCs) consists in the art of thin‐film deposition, with electrodeposition (ED) representing one of the most versatile techniques available. The ED's role in the development of perovskite PV with its advantages, drawbacks, and perspectives is analyzed herein. The ED of inorganic or organic/polymeric selective contacts enables high‐efficiency devices. Moreover, by exploiting properly designed functional barriers it is possible to rely on ED for the metallization of perovskite solar cells through the deposition of copper. The latter aspect could be particularly relevant for the development of silicon/perovskite tandem PV at the TW scale. On the other hand, the ED of the active layer is less successful to date mainly due to solubility issues of the perovskite in electrochemical polar solvents. Abstract : Electrodeposition (ED) is advantageous to prepare the constituents of perovskite solar cells (PSCs) as films coating the PSC charge‐collector. Via ED, selective contacts and perovskite photoactive layers are afforded with a high level of control in terms of morphology, interfacial quality, amount, chemical composition, and electrical properties. The great potential of ED in large‐scale metallization processes of PSCs is recognized.